Dietary Patterns as Determinants of Ferritin Status in Adolescent Girls - Tera Octavia; Ani Margawati; Edward Kurnia Setiawan Limijadi (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Iron deficiency, commonly indicated by low ferritin concentrations, remains a major nutritional problem among adolescent girls and poses risks to growth, cognitive development, and long-term health. While previous studies have largely focused on single nutrients or iron intake, evidence on the relationship between overall dietary patterns and ferritin status among Indonesian adolescents is limited. This study aimed to examine the association between dietary patterns and ferritin status among adolescent girls in Pekalongan, Indonesia. A cross-sectional study was conducted among 80 adolescent girls aged 15–19 years. Serum ferritin levels were measured using ELISA, and dietary patterns were derived using pattern-based dietary assessment. Age, nutrition knowledge, body mass index, physical activity, and hemoglobin concentration were also examined as potential correlates. Dietary pattern was significantly associated with ferritin status, with poorer dietary patterns linked to lower ferritin concentrations. In contrast, no significant associations were observed for body mass index, physical activity, hemoglobin levels, or other individual characteristics, suggesting that overall dietary quality may play a more prominent role in iron stores than single anthropometric or behavioral factors. Given the cross-sectional design and modest sample size, causal inference and generalizability are limited. Nevertheless, the findings highlight the potential value of improving dietary quality through adolescent-focused nutrition education and school-based nutrition strategies to support iron status and reduce the risk of iron deficiency in this population.